Muscle leg strength and muscule arm strength on the power lay-up abillity - Helen Umi Mega Rahayu; Dhias Fajar Widya Permana (Sriwijaya Journal of Sport, 2022)
The aims of this study were (1) to determine the relationship between leg muscles and power lay-up ability; (2) to determine the relationship between arm muscles and power lay-up ability; and (3) knowing the relationship between leg and arm muscles with power lay-up ability in basketball players. This type of research is quantitative research with a descriptive approach and has one dependent variable, namely power lay-up and two independent variables of leg muscles and arm muscles. The sample used was 15 female basketball players at SMK Tamansiswa Banjarnegara. The instruments used were leg dynamometers and pull and push dynamometers. The results of this study are that there is a significant relationship between leg muscle strength and power lay-up ability in female basketball players at SMK Tamansiswa Banjarnegara in the "very poor" category, there is a significant relationship between arm muscle strength and power lay-up abilities in the " sufficient” and there is a significant relationship between leg and arm muscle strength and the ability to lay-up power in the “very poor” category.